2010
DOI: 10.1016/j.jhazmat.2010.01.119
|View full text |Cite
|
Sign up to set email alerts
|

Chlorides behavior in raw fly ash washing experiments

Abstract: Chloride in fly ash from municipal solid waste incinerators (MSWIs) is one of the obstructive substances in recycling fly ash as building materials. As a result, we have to understand the behavior of chlorides in recycling process, such as washing. In this study, we used X-ray absorption near edge structure (XANES) and X-ray diffraction (XRD) to study the chloride behavior in washed residue of raw fly ash (RFA). We found that a combination of XRD and XANES, which is to use XRD to identify the situation of some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 13 publications
1
24
0
1
Order By: Relevance
“…In ash washing experiments, the mole percentage and the amount of soluble chlorides including NaCl, KCl and CaCl 2 decreases quickly with the increase in liquid to solid (L/S) ratio or washing frequency. However, those of insoluble chlorides decrease slower (Zhu et al, 2010).…”
Section: Resultsmentioning
confidence: 93%
“…In ash washing experiments, the mole percentage and the amount of soluble chlorides including NaCl, KCl and CaCl 2 decreases quickly with the increase in liquid to solid (L/S) ratio or washing frequency. However, those of insoluble chlorides decrease slower (Zhu et al, 2010).…”
Section: Resultsmentioning
confidence: 93%
“…Pb and Zn) simultaneously (Quina et al 2008b). Addition of chemical additives or controlling of the pH may overcome this problem (Zhu et al 2010). Water washing can be performed in one step or in several sequential steps; nevertheless, studies have shown that removal of Cl -is more intensive during the first stage and low removal efficiencies are obtained later .…”
Section: Washingmentioning
confidence: 99%
“…Factors, such as L/S ratio, speed and time, have no apparent effect on improving the dissolution of these less soluble components. Zhu et al [21] used X-ray absorption near edge structure(XANES) and XRD to analyze the chloride chemical form and found that insoluble chloride may be present in the form of Friedel's salt (such as [Ca2Al(OH)6]Cl•2H2O) and other insoluble forms related to CaCl2. After the first and second washing, the readily water soluble species (especially chlorides) were greatly leached out (83% for Cl, 26% for Na, 60% for K, 11% for Ca, 8% for S).…”
Section: Double and Triple Washingmentioning
confidence: 99%
“…In Figure 5, no crystalline peaks of CaCl 2 ·2H 2 O and Ca(OH)Cl were found, implying that they may still be present as amorphous and/or complex crystalline phases. Due to the fact that calcium chloride (CaCl 2 ) is hydroscopic and easily forms CaCl 2 ·2H 2 O during the washing process [21], the main phase of Ca, which could be greatly leached out, was CaCl 2 ·2H 2 O rather than CaCl 2 and Ca(OH)Cl. The XRD spectra of the residue after the first and twice washing were nearly unchanged, indicating that the most easily soluble components were already dissolved during the first wash.…”
Section: Double and Triple Washingmentioning
confidence: 99%